Determinants of Financial Management Behaviour among University Students in Kathmandu Valley - Wagle, Gaurab; Pokharel, Utsab (Journal of Business and Social Sciences Research, 2025)
This study attempts to examine the determinants of financial management behaviour among university students in the Kathmandu Valley. The purpose of this study is to examine the influence of financial attitude, financial knowledge, locus of control and mental accounting on financial management behaviour. The explanatory research design was employed in the study to investigate the causal link between financial management behaviour and its determinants. Data, gathered from 205 respondents through a structured questionnaire, utilised convenience sampling. Quantitative analysis involved both descriptive and inferential statistics, employing the PLS-SEM method. Financial knowledge, locus of control and mental accounting had a significant impact on financial management behaviour. However, financial attitude did not have a significant impact on financial management behaviour of university students in Kathmandu valley. For greater assurance of financial management behaviour, the finding could help more targeted and effective financial literacy programs for university students. Nevertheless, the outcome of the study might assist academicians, policymakers, and financial institutions in assisting them to tailor their programs for university students in Kathmandu Valley.